Mortality of anticarsia gemmatalis (Lepidoptera: Noctuidae) caterpillars post exposure to a commercial neem (Azadirachta indica, Meliaceae) oil formulation - Mourão, Sheila Abreu; Zanuncio, José Cola; Tavares, Wagner De Souza; Wilcken, Carlos Frederico [UNESP]; Leite, Germano Leão Demolin; Serrão, José Eduardo (My University, 2014)
The velvetbean caterpillar, Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae), is the most important defoliator of soybean (Glycine max L. Merrill, Fabaceae) crops in Brazil. Early-instar caterpillars of this pest are the main target of control. The objective of this work was to evaluate the toxicity of a commercial product, Bioneem® [neem oil (Azadirachta indica A. Juss., Meliaceae)], sprayed on A. gemmatalis caterpillars. Bioneem® was sprayed on soybean plants and 3 h later specific branches were enclosed by organza bags in a greenhouse with third-instar A. gemmatalis caterpillars. Ten replications with 80 caterpillars were used per treatment. The mortalities of A. gemmatalis caterpillars (mean 3rd to 6th instars) was 3.17, 7.18, 5.00, 11.25, 16.74, and 18.15%, whereas the respective mortalities of the pupae obtained from treated the caterpillars were 20.57, 22.79, 29.64, 39.16, 51.50, and 59.17%. The viabilities until the pre-pupal stage were 76.26, 70.03, 65.36, 49.59, 31.76, and 22.68% with 2.5, 5, 10, 15, 20, and 25% of the neem oil, respectively. The larval stage of this pest (3rd instar to pre-pupa) lasted longer in the 20% neem oil treatment than at the other rates, but its longevity was not affected. Anticarsia gemmatalis pupae presented developmental interruptions and anomalies at all concentrations of neem oil. The commercial product Bioneem® (neem oil) can therefore be used as a suitable alternative to synthetic insecticides to control A. gemmatalis.
Keywords: alternative control; botanical insecticide; defoliator; soybean; velvetbean caterpillar